Auditory brainstem response: A diagnostic tool: Three case reports - (:unkn) unknown (My University, 1996)
The sensitivity of Auditory Brainstem Response (ABR) audiometry is high for detecting the 8th cranial nerve (N VIII) tumors. With the routine use of ABR the sensitivity and specificity of the test will be higher. We present three cases which illustrate the value of ABR as a diagnostic tool. The results of ABR were positive in all three cases and were verified by Magnetic Resonans Imaging (MRI) and surgery. The role of ABR testing in diagnosis is undeniable with its being noninvasive and an easy to use technique.
Keywords: Auditory brainstem response; Cerebellopontine angle tumors; Neural pathology; Retrocochlear pathology